Adenosinergic Signalling in Cervical Cancer Microenvironment - Isabele Cristiana Iser; Ana Paula Santin Bertoni; Liziane Raquel Beckenkamp; Marcia Edilaine Lopes Consolaro; Silvya Stuchi Maria-Engler; Marcia Rosângela Wink (Expert Reviews in Molecular Medicine)
Despite the emergence of the first human papillomavirus vaccine, the incidence of cervical cancer is still responsible for more than 350,000 deaths yearly. Over the past decade, ecto-5′-nucleotidase (CD73/5′-NT) and extracellular adenosine (ADO) signalling has been the subject of many investigations to target cancer progression. In general, the adenosinergic axis has been linked to tumourigenic effects. However, CD73 can play contradictory effects, probably dependent on the tumour type, tumour microenvironment and tumour stage, thus being in some circumstances, inversely related to tumour progression. We herein reviewed the pathophysiological function of CD73 in cervical cancer and performed in silico analysis of the main components of the adenosinergic signalling in human tissues of cervical cancer compared to non-tumour cervix tissue. Our data showed that the NT5E gene, that encoded CD73, is hypermethylated, leading to a decreased CD73 expression in cervical cancer cells compared to normal cells. Consequently, the high availability of ADO cytoplasmatic/extracellular leads to its conversion to AMP by ADK, culminating in global hypermethylation. Therefore, epigenetic modulation may reveal a new role for CD73 in cervical cancer.